Cyclopropane-1, 2-dicarboxylic acids as new tools for the biophysical investigation of O-acetylserine sulfhydrylases by fluorimetric methods and saturation transfer difference (STD) NMR. (4th November 2016) - Annunziato, Giannamaria; Pieroni, Marco; Benoni, Roberto; Campanini, Barbara; Pertinhez, Thelma A.; Pecchini, Chiara; Bruno, Agostino; Magalhães, Joana; Bettati, Stefano; Franko, Nina; Mozzarelli, Andrea; Costantino, Gabriele
Abstract: Cysteine is a building block for many biomolecules that are crucial for living organisms. O -Acetylserine sulfhydrylase (OASS), present in bacteria and plants but absent in mammals, catalyzes the last step of cysteine biosynthesis. This enzyme has been deeply investigated because, beside the biosynthesis of cysteine, it exerts a series of "moonlighting" activities in bacteria. We have previously reported a series of molecules capable of inhibiting Salmonella typhimurium ( S. typhymurium ) OASS isoforms at nanomolar concentrations, using a combination of computational and spectroscopic approaches. The cyclopropane-1, 2-dicarboxylic acids presented herein provide further insights into the binding mode of small molecules to OASS enzymes. Saturation transfer difference NMR (STD-NMR) was used to characterize the molecule/enzyme interactions for both OASS-A and B. Most of the compounds induce a several fold increase in fluorescence emission of the pyridoxal 5′-phosphate (PLP) coenzyme upon binding to either OASS-A or OASS-B, making these compounds excellent tools for the development of competition-binding experiments.